Artificial Intelligence And The Transformation Of English Language Studies: A Bibliometric Perspective (2018–2025) - Tong, Thanh Thuy (International Journal of Scientific Research and Management (IJSRM), 2025)
Artificial intelligence (AI) is reshaping English language studies at an unprecedented pace, particularly since the emergence of generative models such as ChatGPT in 2022. It should be emphasized that although the number of academic publications in this domain has risen rapidly, large-scale bibliometric syntheses remain scarce, leaving research trends, thematic clusters, and knowledge gaps insufficiently systematized. This study draws on Scopus data from 2018 to 2025, applying Bibliometrix and VOSviewer to analyze 850 cleaned records. Findings confirm that publication output has grown exponentially, with a dramatic surge in 2024–2025; journals such as Education and Information Technologies and Computer Assisted Language Learning stand out as leading outlets; and the most influential scholars are concentrated in China, South Korea, and the United States, while country collaboration networks reveal a distinctly multipolar structure. Notably, keyword mapping and thematic evolution indicate a shift from traditional tools such as machine translation and intelligent tutoring systems toward emerging topics including ChatGPT, automated feedback, and online learning. In other words, the study not only consolidates evidence of the field’s rapid transformation but also suggests future research directions, including extending inquiry to multiple language skills, developing integrative theoretical frameworks, and advancing cross-cultural empirical studies. Taken together, these contributions provide value for both academics and policymakers seeking to integrate AI into foreign language education strategies in an effective and sustainable manner.